PHYSICHOCHEMICAL CHACTERIZATION OF BACTERIOCIN PRODUCING ENTEROCOCCUS DURANS ISOLATED FROM COLON’S BALI CATTLE - Suardana, I Wayan; Septiara, Hana Kristal Alamanda; Suarsana, I Nyoman (Buletin Veteriner Udayana; Vol. 9 No. 2 Agustus 2017, 2017)
Lactic acid bacteria can excrete antimicrobial compounds like bacteriocins. The study  aimed  to  find  out  the  characteristic  of  physic-chemical  of  bacteriocin  producing Enterococcus durans          isolate 18A isolated from  colon’s bali cattle. The study initiated by Gram staining and catalase test, followed by isolation and purification  of bacteriocin.       The result of the research showed  that bacteriocins of    Enterococcus durans     isolate 18A as a protein with it’s concentrationis  0,272?g/ml  and  it  does  not  contain  carbohydrate.  On  the  other  hand,  the bacteriocins was not showed a band while tested on sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The result showed, the bacteriocin producing            Enterococcus durans isolate 18A has antimicrobial activity to Bacillus cereus  as 23,88%.